Relationship between Contingent Negative Variation and afterimage duration in migraine patients - Giesen, Simeon; Rimmele, Florian; Jürgens, Tim P.; Scheidt, Jörg; Drescher, Johannes; Leonhardt, Ann-Kristin; Schulze, Sophia; Harbeck, Birgit; Meyer, Wolfgang; Müller, Britta; Kropp, Peter; Keller, Armin (Frontiers in Neurology, 2024)
Background Abnormalities in electrocortical parameters and persistence of afterimage after visual stimulation are known to occur in migraine patients. The results of studies on Contingent Negative Variation (CNV) and afterimage persistence in migraine patients suggest a link between these two phenomena and a connection to the pathomechanism of migraine. Objectives To date, no studies have investigated both afterimage duration and CNV parameters in the same subjects. The aim of this study was to investigate the relationship between the early component of CNV (iCNV) and the duration of the afterimage in migraine patients. Methods Sixty seven migraine patients from the headache center of the University of Rostock Medical Center were examined for iCNV amplitude, iCNV habituation and afterimage duration. The subjects also completed questionnaires developed for this study and the MIDAS (Migraine Disability Assessment) questionnaire. Results Associations were found between iCNV amplitude and afterimage duration and between habituation capacity and afterimage duration. A deficit in habituation capacity correlated with a significantly prolonged afterimage duration. Increased iCNV amplitude and prolonged afterimage duration were also significantly correlated. Conclusion Conclusions about the pathophysiology of migraine can be drawn from the results of this study. The results support the hypothesis of cortical hyperexcitability as a consequence of a low pre-activation level, which may be a possible contributory cause of migraine. Furthermore, they allow assessment of whether the afterimage examination, which is easier and quicker to perform than the CNV examination, can be used as a diagnostic tool or as a parameter to monitor the course of therapy in people with migraine.